2021
DOI: 10.3390/cancers13143420
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation of Very-Early- and Early-Stage HCC: Efficacy Evaluation by Correlation with Histology after Liver Transplantation

Abstract: Microwave (MW) ablation is a worldwide-diffused technique for the percutaneous ablation of hepatocellular carcinoma (HCC). Nevertheless, the efficacy of this technique still needs to be confirmed in pathological specimens. The purpose of this study was to evaluate the efficacy of MW ablation by correlation with histology in excised liver samples at the time of liver transplantation (LT). All patients with MW-ablated HCC who subsequently underwent LT between 2012 and 2020 were retrospectively evaluated. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In a recent retrospective study including 40 HCC nodules percutaneously treated with MWA in patients who subsequently underwent LT, complete and partial necrosis were found in 77.8% and 22.2% of cases, respectively, at the excised liver after LT [ 45 ]. These results were obtained with a single MWA session, whereas often in RFA series the treatment is applied two, or even three, times [ 36 , 37 , 45 ].…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…In a recent retrospective study including 40 HCC nodules percutaneously treated with MWA in patients who subsequently underwent LT, complete and partial necrosis were found in 77.8% and 22.2% of cases, respectively, at the excised liver after LT [ 45 ]. These results were obtained with a single MWA session, whereas often in RFA series the treatment is applied two, or even three, times [ 36 , 37 , 45 ].…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…MWA is a widely used thermal ablation modality for eradicating malignant cells with minimal damage to the surrounding tissues [ 32 , 33 , 34 ]. It consists in focusing an energy source in the target zone (the tumoral tissue) causing tumor destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, multiple studies have demonstrated that percutaneous ultrasound and/or CT‐guided radiofrequency (RFA) or microwave are safe and effective for bridging to transplant with high rate of complete pathologic necrosis (>75%) either (1) after initial downstaging with TACE to within Milan criteria or (2) for patients initially within Milan criteria with very early or early stage HCC. [ 35–40 ] However, for HCC >2–3 cm and/or located near large blood vessels, rates of complete pathologic necrosis after ablation with standard imaging and guidance techniques have historically been lower (30%–55%). [ 38 ] Nonetheless, Bale et al [ 41 ] performed an important study examining percutaneous stereotactic radiofrequency ablation as bridging therapy to transplant in 97 patients with 195 HCC nodules (median tumor size was 2.5 cm; range, 1–8 cm).…”
Section: Downstaging Using Nonsystemic Approach—lrtmentioning
confidence: 99%